Problem based learning on wetland socioscientific issue: A pathway to enhance scientific literacy and collaborative skill - Nurul Hidayati Utami; Kaspul Kaspul; Aminuddin Prahatama Putra; Bunda Halang; Amalia Rezeki (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Addressing the demands of 21st-century competencies, this study analyzed the influence of integrating Problem-Based Learning (PBL) with Socio-scientific Issues (SSI) on students' cognitive learning outcomes in Biology and examined its effectiveness in enhancing students' collaboration skills, particularly within the context of South Kalimantan's wetland ecosystems. Employing a quasi-experimental pretest-posttest design involving 120 students from MAN 2 and SMA 11 Banjarmasin, data were collected using validated instruments. Results from the Wilcoxon Signed-Rank test indicated a significant improvement in scientific literacy (p < 0.001), while the Mann-Whitney U test revealed a significant enhancement in collaboration skills (p < 0.001) within the PBL-SSI group compared to direct instruction. These findings affirm that PBL-SSI effectively addresses the limitations of traditional models in developing essential 21st-century competencies. This approach specifically fosters active learning, teamwork, and concurrently enhances student engagement and environmental awareness. It is concluded that integrating SSI into PBL creates a more meaningful and impactful learning experience, equipping students to tackle complex socio-scientific problems in the future.Abstrak. Menjawab tuntutan kompetensi abad ke-21, penelitian ini menganalisis pengaruh integrasi Problem-Based Learning (PBL) dengan Socio-scientific Issues (SSI) terhadap hasil belajar kognitif siswa dalam Biologi dan menguji efektivitasnya dalam meningkatkan keterampilan kolaborasi siswa, khususnya dalam konteks ekosistem lahan basah Kalimantan Selatan. Menggunakan desain kuasi-eksperimen pretest-posttest dengan 120 siswa dari MAN 2 dan SMA 11 Banjarmasin, data dikumpulkan melalui instrumen tervalidasi. Hasil uji Wilcoxon Signed-Rank menunjukkan peningkatan signifikan pada literasi sains (p < 0.001), sementara uji Mann-Whitney U mengindikasikan peningkatan signifikan pada keterampilan kolaborasi (p < 0.001) dalam kelompok PBL-SSI dibandingkan instruksi langsung. Temuan ini menegaskan bahwa PBL-SSI secara efektif mengatasi keterbatasan model tradisional dalam mengembangkan kompetensi abad ke-21. Pendekatan ini secara spesifik mendorong pembelajaran aktif, kerja tim, serta meningkatkan keterlibatan siswa dan kesadaran lingkungan. Disimpulkan bahwa integrasi SSI ke dalam PBL menciptakan pengalaman belajar yang lebih bermakna dan berdampak, menyiapkan siswa menghadapi masalah sosio-ilmiah kompleks di masa depan.